Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1186/1471-2105-9-472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GO-based functional similarity measures using S. cerevisiae protein interaction and expression profile data

Abstract: BackgroundResearchers interested in analysing the expression patterns of functionally related genes usually hope to improve the accuracy of their results beyond the boundaries of currently available experimental data. Gene ontology (GO) data provides a novel way to measure the functional relationship between gene products. Many approaches have been reported for calculating the similarities between two GO terms, known as semantic similarities. However, biologists are more interested in the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 30 publications
(38 reference statements)
3
65
1
Order By: Relevance
“…The evaluation of these methods shows that the similarity obtained using the 'Max' method is best correlated with the gene expression data. However, the 'Max' method is more sensitive to outliers, while the 'Ave' method is relatively stable (Xu et al, 2008).…”
Section: Measuring Semantic Similarity On Gomentioning
confidence: 99%
See 3 more Smart Citations
“…The evaluation of these methods shows that the similarity obtained using the 'Max' method is best correlated with the gene expression data. However, the 'Max' method is more sensitive to outliers, while the 'Ave' method is relatively stable (Xu et al, 2008).…”
Section: Measuring Semantic Similarity On Gomentioning
confidence: 99%
“…In our experiments, we used the annotations from BP ontology. According to (Xu et al, 2008), terms at the top levels will create noise. Therefore, in our experiments, annotations at the first three levels were removed.…”
Section: Data Description and Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Guo et al compared a number of network-based and information content-based semantic similarity methods in distinguishing true and false human PPIs, and concluded that the average (AVG) method by Resnik performed best in AUROC analysis [55][56][57][58]. Xu et al compared the AVG and maximum (MAX) methods by Resnik to a number of semantic similarity methods specifically developed for GO, and concluded that the MAX method by Resnik outperforms others when considering the three ontologies of GO either individually or together [55,[59][60][61][62]. More recently, our group developed the Topological Clustering Semantic Similarity (TCSS) method, which uses a novel normalization technique before computing similarity [63].…”
Section: Cellular Location Biological Process Molecular Functionmentioning
confidence: 99%